Wanita dan Entrepreneurship Rumahan Melalui Manajemen Posyandu di Jombang Ciputat - Halim Tjiwidjaja; Sutariyono Sutariyono; Aep Saefullah (OPTIMAL Jurnal Ekonomi dan Manajemen, 2023)
The current less than favorable economic conditions require people to play an active role in fulfilling their daily needs. Empowering women through the MSME sector is expected to help increase income, reduce poverty levels, increase knowledge and quality of human resources and prepare women's communities to become home-based entrepreneurial communities that can help support the family economy and contribute to improving community welfare and the national economy. Economic empowerment/entrepreneurship through women's activity groups such as posyandu groups is a form of effort or process to increase awareness, willingness to improve the economy or family (community) standard of living. The research method used by researchers is a descriptive method with a qualitative approach, collection techniques using observation techniques and interview techniques with women members of posyandu in Jombang, South Tangerang. The aim of this research is to describe how interested posyandu members are in entrepreneurship to develop the community economy which has implications for reducing poverty and increasing community welfare. The research results showed that the counseling participants strongly agreed that to improve welfare/reduce poverty, you must open a home business. This is shown by the enthusiasm and enthusiasm of the counseling participants and the questions asked regarding how posyandu members/women start home businesses.